2013
DOI: 10.1016/s2221-1691(13)60042-8
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic potential of snake venom in cancer therapy: current perspectives

Abstract: Many active secretions produced by animals have been employed in the development of new drugs to treat diseases such as hypertension and cancer. Snake venom toxins contributed significantly to the treatment of many medical conditions. There are many published studies describing and elucidating the anti-cancer potential of snake venom. Cancer therapy is one of the main areas for the use of protein peptides and enzymes originating from animals of different species. Some of these proteins or peptides and enzymes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
76
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 130 publications
(87 citation statements)
references
References 53 publications
0
76
0
6
Order By: Relevance
“…For instance, recent studies have demonstrated that the usage of various anti-VEGF/PDGF strategies is linked to an increased risk of early metastasis in animal cancer models. Although the clinical relevance of these preclinical studies is not yet clear, these data support the idea that not only is there an imperative need to design novel anti-angiogenic drugs with better anti-invasive properties, also to test the impact of standard of care anti-angiogenics such as Avastin on metastasis [30][31][32][33][34][35][36][37][38][39][40].…”
Section: Cr Venom Of Vn Was Collected Lyophilized Successfullymentioning
confidence: 94%
See 1 more Smart Citation
“…For instance, recent studies have demonstrated that the usage of various anti-VEGF/PDGF strategies is linked to an increased risk of early metastasis in animal cancer models. Although the clinical relevance of these preclinical studies is not yet clear, these data support the idea that not only is there an imperative need to design novel anti-angiogenic drugs with better anti-invasive properties, also to test the impact of standard of care anti-angiogenics such as Avastin on metastasis [30][31][32][33][34][35][36][37][38][39][40].…”
Section: Cr Venom Of Vn Was Collected Lyophilized Successfullymentioning
confidence: 94%
“…Therefore, since 2001, the scientific research collaboration between VN and University of Southern California (USC) was established. Since 2014 this project has been approved by VN government [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40]. …”
mentioning
confidence: 99%
“…It produces toxicity only if contacted with blood. 8 This is very well understood by our ancient Acharya. So that Acharya Vagbhata used snake venom in various diseases which has been elaborated in 48 th chapter of Uttartantra of Ashtanga Sangraha, i.e.…”
Section: Introductionmentioning
confidence: 91%
“…Induction of apoptosis is the most important mechanism for many anticancer agents. In fact, an ideal anticancer agent mostly potentiates apoptotic effects in cancer cells [37]. Fluorescence microscopic analysis of cell death showed that treatment of cells with compounds induce more apoptotic cell death rather than necrotic death.…”
Section: Fluorescence Microscopic Analysis Of Cell Deathmentioning
confidence: 99%